Effect of visceral fat tissue on superior mesenteric artery configuration: Is it superior to BMI? - Bahadir Ülger, Fatma Esra (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To determine the effect of visceral fat volume measured via CT images of umbilical slices on superior mesenteric artery (SMA) configuration, as compared to BMI. Also to determine the effect of lumbar lordosis angle (LLA) on SMA configuration. Materials and Methods: The study included 310 patients that underwent abdominal CT. On CT images the aortomesenteric angle (AMA), the distance between SMA and aorta at 3 levels, and LLA were measured. Visceral fat volume was measured using 3 consecutive images obtained at the level of the umbilicus. The relationship between AMA, and distances measured between SMA and aorta, and visceral fat tissue volume were determined. The effect of LLA on AMA and distances measured between SMA and aorta was analyzed. Results: There was a significant positive correlation between visceral fat volume, and patient age, AMA, distances between SMA and aorta, LLA, and BMI (p<0.001). There weren’t any significant differences in AMA, distances between SMA and aorta, BMI, or visceral fat volume between the patients with an LLA of 20°-45° and those with an LLA>45° (p>0.05). There was a significant positive correlation between BMI, and AMA, distances between SMA and aorta (p<0.001). There was a significant positive correlation between visceral fat volume, and AMA, distances between SMA and aorta (p<0.001). Conclusion: Visceral fat tissue volume is more valuable than BMI for evaluating the SMA configuration.